Etika Bisnis Islam Dalam Pemanfaatan Media Sosial Sebagai Strategi Pemasaran UMKM Usaha Toko Baju Thrifting - Ulya Nindyaningtyas (Program Studi Perbankan Syariah Institut Al-Fithrah (IAF) Surabaya, 2025)
This research discusses the application of Islamic business ethics in digital marketing strategies among MSMEs, especially second-hand clothing stores, by utilizing social media. Advances in digital technology allow MSMEs to promote products effectively, but these marketing strategies must be aligned with Islamic principles, such as honesty, transparency, and fairness. The study identified challenges such as a lack of understanding of digital marketing and limited resources, which hindered MSME engagement with consumers. Emphasis is placed on the importance of maintaining honest marketing messages to build customer trust and loyalty. Creative content and direct communication through social media, such as WhatsApp, are considered effective for increasing customer engagement and strengthening brand image.